The role of microRNA156-regulated SQUAMOSA PROMOTER BINDING PROTEINS in the control of shoot branching in tomato - Brito, Diêgo Armando Pinheiro (2020)
The formation of branches is one of the key determinants of shoot architecture, determining how plants grow and having direct impacts in their productivity. Lateral branches originate from axillary meristems, formed in the axils of each leaf primordia. Once established, axillary meristems give rise to a few lead primordia, giving rise to an axillary bud. Depending on the plants developmental program and on environmental conditions, axillary buds may remain dormant or outgrow, forming a new lateral branch. Several transcription factors, phytohormones, metabolites and environmental signals have been associated with the formation of axillary meristems or with the regulation of axillary bud activity. Members of the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE (SPLs/SBPs) family of transcription factors regulated by the microRNA156 (miR156) have emerged as potential regulators of shoot architecture, regulating both the formation of axillary meristems and the activity of axillary buds. In this work, we: (1) review recent literature on the effects of the main endogenous and environmental signals controlling the formation of axillary meristems and activity of axillary buds and; (2) investigated the role of miR156-targeted SlSBPs in the control of shoot branching in tomato, demonstrating an interaction between the miR156/SBP module and auxin and cytokinin signalling, besides a possible interaction with other transcription factors controlling the activity of axillary buds.